Oncolytic virotherapy against lung cancer: key receptors and signaling pathways of viral entry - Dong, Wenxun; Luo, Ying; He, Daqian; Zhang, Ming; Zeng, Jingtong; Chen, Ying (Frontiers in Immunology, 2024)
Lung cancer accounts for the highest cancer-related mortality worldwide. While immunotherapies targeting anti-tumor immune responses have demonstrated efficacy in clinical practice, the demand for novel treatment modalities remains urgent. Oncolytic viruses (OVs), which selectively kill tumor cells while stimulating an anti-tumor immune response, represent a potential breakthrough in lung cancer therapy. The induction of anti-tumor immunity by OVs is central to their overall therapeutic effectiveness. Many natural receptors on the surface of cancer cells are dysregulated, providing potential entry points for OVs. Furthermore, the inherent dysregulation of some key signaling pathways in lung cancer cells promotes proliferation, progression and metastasis, which may facilitate selective viral replication. In this review, we explore the application of OVs in lung cancer by analyzing several major OVs and their corresponding entry receptors. Then, we also examine the key signaling pathways and molecules with the potential to synergize with OVs in modulating the immune tumor microenvironment. Finally, we discuss the combination and administration strategies that warrant further clinical trials for validation. Despite certain limitations, the tolerability of OVs positions virotherapy as a promising avenue in the future of lung cancer treatment.